Rally for Albert Luthuli on award of Nobel Peace Prize. In Cape Town. Albert Leftwich, NUSAS-president, speaks
Rally for Albert Luthuli on award of Nobel Peace Prize. In Cape Town. Albert Leftwich, NUSAS-president, speaks.